Alemtuzumab vs anti‐thymocyte globulin in patients transplanted from an unrelated donor after a reduced intensity conditioning. (18th September 2018) - Robin, Marie; Raj, Kavita; Chevret, Sylvie; Gauthier, Jordan; de Lavallade, Hugues; Michonneau, David; McLornan, Donal; Peffault de Latour, Régis; Potter, Victoria; Kulasekararaj, Austin; Sicre de Fontbrune, Flore; Pagliuca, Antonio; et al.
Abstract: Objective: Relapse and graft‐vs‐host disease (GVHD) are still the main complications after allogeneic hematopoietic stem cell transplantation, especially in the setting of reduced intensity regimen (RIC) and unrelated donor. We compared here anti‐thymocyte globulin (ATG) or alemtuzumab as GVHD prophylaxis in patients with myeloid disease transplanted after RIC and from an unrelated donor. Method: ATG and alemtuzumab patients have been matched by age, gender, HLA matching, comorbidities and cytogenetics risk (119 patients in each group). Results: After matching, we found that ATG decreased the risk of relapse (HR: 0.55, P  = .0049) and improved relapse‐free survival (RFS, HR: 0.70, P  = .042). The improved RFS with ATG was more pronounced in CMV‐positive patients but was not influenced by disease risk. Regarding overall survival, GVHD‐free relapse‐free survival and transplant‐related mortality, the risk was similar using ATG or alemtuzumab. Conclusion: Even if GVHD risk is lowered by alemtuzumab use, it does not translate in better outcome due to higher risk of relapse.